AN ANALYSIS OF INTERNAL AND EXTERNAL CONFLICTS OF THE MAIN CHARACTER IN SOHN WON PYUNG’S ALMOND - Yusuf, Niken; Sabudu, Delli; Maukar, Merlin M. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
This research aims to explain the conflicts experienced by the main character and how to resolve each conflict in his life. The problem examined in this research is the internal and external conflict of the main character in the novel Almond by Sohn Won Pyung. This research uses data sourced from the novel Almond and then analyzed using qualitative methods with a Sigmund Freud-style literary psychology approach, namely the theory of the id, ego and superego. The analysis results obtained show that overall the problems experienced by the main character are the Id, attitudes that arise naturally, as a result of encouragement and cooperation, the Id works based on the principle of pleasure. The id makes decisions or desires without considering rationality. Ego is an action that unconsciously obtains momentary pleasure or enjoyment by prioritizing only needs, and Superego is a temporary action regarding decisions regarding the value of right or wrong in all things. awareness without regret and bear all the consequences of the actions taken